Strategi Pembelajaran Berbasis Digital dalam Meningkatkan Kualitas Pembelajaran - Muftiatul Husna (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2024)
Digitalization in the education sector has brought various digital-based learning methods that are able to improve the quality of the teaching and learning process. This research aims to review effective digital learning strategies in supporting educational quality. The research was conducted using a literature study with a descriptive approach, collecting references from journals, books and related research reports. Research findings show that the use of technology such as e-learning, interactive learning applications, and the integration of social media in learning activities can increase student participation, enrich learning resources, and provide flexibility in the learning process. This strategy also helps overcome several obstacles to conventional learning, such as limited space and time. However, barriers such as unequal access to technology and students' digital skills remain challenges that need to be overcome. Overall, digital-based learning has proven effective in improving the quality of education, but requires adequate infrastructure support and increasing digital literacy for all parties involved in the world of education.